(untitled) (International Seven Journal of Multidisciplinary, 2024)
The aim of this study was to identify the level of knowledge and practice of social skills, assertiveness, teamwork and self-control/emotional expressiveness in children taking part in the "Full-Time Project" at the Valdir Gonçalves de Lima CEM, in the municipality of Votuporanga-SP. The work is characterized as exploratory of a quantitative and qualitative nature, through pre-post tests and field diaries on the play activities proposed in order to identify the children’s knowledge of the chosen skills. The study showed that those surveyed already had an understanding of the social skills in question, since they already had a certain degree of knowledge in the pre-test, with no significant evolution in the post-test, but even though they had knowledge of the subject, they were unable to apply it in their daily school and family life. In this way, the objectives were achieved by creating a bond, showing practical ways of using social skills and making the participants learn about the proposed topic in a fun and entertaining way.